2012
DOI: 10.1364/ao.51.004003
|View full text |Cite
|
Sign up to set email alerts
|

Hardware architecture of high-performance digital hologram generator on the basis of a pixel-by-pixel calculation scheme

Abstract: In this paper we propose a hardware architecture for high-speed computer-generated hologram generation that significantly reduces the number of memory access times to avoid the bottleneck in the memory access operation. For this, we use three main schemes. The first is pixel-by-pixel calculation, rather than light source-by-source calculation. The second is a parallel calculation scheme extracted by modifying the previous recursive calculation scheme. The last scheme is a fully pipelined calculation scheme and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…107 Seo et al proposed a hardware architecture based on pixel-by-pixel calculation scheme. 87,88,92,95 In this line of work, the authors efficiently reduced the number of memory accesses by utilizing the pixel-by-pixel method, which is different from the conventional light source-by-source calculation method. The authors also demonstrated a VLSI chip, based on the proposed FPGA architecture.…”
Section: Advantages and Disadvantages Of Using Fpgasmentioning
confidence: 99%
“…107 Seo et al proposed a hardware architecture based on pixel-by-pixel calculation scheme. 87,88,92,95 In this line of work, the authors efficiently reduced the number of memory accesses by utilizing the pixel-by-pixel method, which is different from the conventional light source-by-source calculation method. The authors also demonstrated a VLSI chip, based on the proposed FPGA architecture.…”
Section: Advantages and Disadvantages Of Using Fpgasmentioning
confidence: 99%
“…This section describes the CGH calculation method [2][3][4][5] and the method using a recursive addition system. The CGH generating equation is defined as Eq.…”
Section: Computer-generated Hologrammentioning
confidence: 99%
“…Seo et al also implemented FPGA boards for CGH computation. [19]. All the above parallel computation procedures used parallelism either in the hologram plane or in the object plane, but never both.…”
Section: Introductionmentioning
confidence: 99%